Monosodium glutamate (MSG) exposure induced oxidative stress and disrupted testicular hormonal regulation, exacerbating reproductive dysfunction in male WISTAR rats - Adesua Emmanuel Ogunmokunwa; Babatunde Oluwaseun Ibitoye (Endocrine and Metabolic Science)
Background: Monosodium glutamate (MSG) is a common food additive linked to various health concerns, including potential reproductive toxicity. Objective: To investigate the effects of chronic, low-dose MSG on testicular hormones and oxidative stress biomarkers in adult male Wistar rats. Methods: Thirty male Wistar rats were divided into five groups (n = 6 per group). The control group received distilled water, while the experimental groups were orally administered MSG at 30, 100, 300, and 1000 mg/kg body weight for 65 days. Hormonal levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone were measured using ELISA. Testicular oxidative stress markers, including malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were assessed. Results: MSG caused a dose-dependent decrease in LH, FSH, and testosterone levels, with the highest dose (1000 mg/kg) exhibiting the most significant reductions. MDA levels increased proportionally with MSG dosage, indicating heightened oxidative stress. Conversely, the activities of antioxidant enzymes (SOD, CAT, GSH, GPx) were significantly diminished, reflecting impaired antioxidant defences. Conclusion: Chronic MSG exposure disrupts hormonal regulation and induces oxidative stress in a dose-dependent manner, potentially impairing male reproductive health. These findings underscore the need for further studies on the long-term reproductive effects of MSG and possible protective interventions.